2016
DOI: 10.1056/nejmoa1510795
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Late Mortality among 5-Year Survivors of Childhood Cancer

Abstract: Background Previously, eighteen percent of childhood cancer patients who survived five years died within the subsequent 25 years. In recent decades, cancer treatment regimens have been modified with the goal of reducing risk for life-threatening late effects. Methods Late mortality was evaluated in 34,033 five-year survivors of childhood cancer (diagnosed <21 years of age from 1970-1999, median follow-up 21 years, range 5-38). Demographic and disease factors associated with mortality due to health-related ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
432
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 490 publications
(456 citation statements)
references
References 39 publications
16
432
6
2
Order By: Relevance
“…3 Weight status was defined as underweight if BMI (kg/m 2 ) ,18.5, normal weight if BMI = 18.5-24.9, overweight if BMI = 25-29.9, and obese if BMI $30. 4 Height was assessed by SDS. Raw height was converted to SDS by comparing the height of the survivors with the mean height of a reference population (i.e., the 2000 CDC growth chart).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Weight status was defined as underweight if BMI (kg/m 2 ) ,18.5, normal weight if BMI = 18.5-24.9, overweight if BMI = 25-29.9, and obese if BMI $30. 4 Height was assessed by SDS. Raw height was converted to SDS by comparing the height of the survivors with the mean height of a reference population (i.e., the 2000 CDC growth chart).…”
Section: Discussionmentioning
confidence: 99%
“…However, after successful treatment, childhood cancer survivors experience a substantially higher risk of premature mortality and serious morbidity at a young age (2)(3)(4). Nutrition is among the few modifiable factors that can prevent or delay the early onset of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, childhood cancer treatment protocols have been modified, aiming to reduce the occurrence and severity of long-term treatment-related complications. Recently, Armstrong and coworkers demonstrated that these efforts resulted in improved long-term survival (Armstrong et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After 25 years of follow-up since primary cancer diagnosis, secondary malignant neoplasms even become the most important cause of death in survivors of childhood cancer (Mertens et al 2008, Reulen et al 2010. Although mortality attributable to secondary malignancies in childhood cancer survivors declined over the past treatment eras (Armstrong et al 2016), the risk for developing a solid secondary malignant neoplasm did not (Schaapveld et al 2015). Endocrine-related cancers are among the most common secondary malignancies in childhood cancer survivors (Inskip & Curtis 2007, Olsen et al 2009, Friedman et al 2010, Reulen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Развитие осложнений ТГСК в посттрансплан-тационном периоде (ПТП) может быть связано с характеристиками заболевания и преморбидными факторами, особенностями пациента (возраст, пол, генетические особенности), осложнениями, приобре-тенными на фоне терапии (химио-(ХТ) и иммуноте-рапия, хирургическое лечение, облучение), и после-дующей ТГСК, а также с посттрансплантационными иммуноопосредованными изменениями [8,9].…”
unclassified